2008
DOI: 10.1007/s10585-008-9195-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new orthotopic animal model of metastatic liver cancer in the rabbit VX2 model: effect on metastases after partial hepatectomy, intra-arterial treatment with 3-bromopyruvate and chemoembolization

Abstract: The VX2 rabbit model of liver cancer is a suitable model to compare the influence of partial hepatectomy, intra-arterial treatment with 3-BrPA and TACE on tumor recurrence in the form of regional and distant metastases. Our results indicate that intra-arterial delivery of 3-BrPA may result in a favorable metastatic profile when compared to both liver resection and TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In addition, the high local tumor control rate was confirmed by FDG-PET scans and yielded significant survival benefits for intra-arterially treated animals [68]. This rare ability of an investigative drug to achieve survival benefits in an animal tumor model was also confirmed in other animal studies, making 3-BrPA a promising candidate for clinical trials [69,70]. Additionally, another comparative trial demonstrated the encouraging potential of intra-arterial 3-BrPA infusions to effectively prevent intra-abdominal metastatic spread of VX2 tumors, known for a aggressive growth pattern [71].…”
Section: Targeting Cancer Metabolismmentioning
confidence: 89%
“…In addition, the high local tumor control rate was confirmed by FDG-PET scans and yielded significant survival benefits for intra-arterially treated animals [68]. This rare ability of an investigative drug to achieve survival benefits in an animal tumor model was also confirmed in other animal studies, making 3-BrPA a promising candidate for clinical trials [69,70]. Additionally, another comparative trial demonstrated the encouraging potential of intra-arterial 3-BrPA infusions to effectively prevent intra-abdominal metastatic spread of VX2 tumors, known for a aggressive growth pattern [71].…”
Section: Targeting Cancer Metabolismmentioning
confidence: 89%
“…In the last 10 years, the medical science has been noticing even more the potential of the white rabbit (Oryctolagus cuniculus) of the New Zealand lineage 1 as an experimental animal model for the research in video-surgery, general surgery, orthopedics, gynecology, vascular, craniofacial and urologic [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . However, there are few information with a good scientific evidence, regarding the perioperative care [2][3][4][5][6][7][8][9][10][11][12][13][14][15]17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few information with a good scientific evidence, regarding the perioperative care [2][3][4][5][6][7][8][9][10][11][12][13][14][15]17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a glycolytic inhibitor, "3BP is a fast acting, promising, powerful, specific and effective anti-cancer agent", said by Pedersen 3 . Also 3BP has been identified to inhibit tumor cells proliferation as a proposed widely used anti-cancer agent 4 , such as in breast cancer cells 5,6 , liver cancer cells 7,8 , lymphoma cells 9 , lung cancer cells 10 , pancreatic cancer cells 11,12 , gastric cancer 2,13 , colorectal cancer cells 14 . Those significant anti-tumor effects of 3BP has made it getting more and more attention 15,16 .…”
mentioning
confidence: 99%